Regular form-based sliding mode control design on a two-wheeled inverted pendulum. (23rd March 2022) - Yang, Yankun; Yan, Xinggang; Sirlantzis, Konstantinos; Howells, Gareth
In this paper, a Lagrangian-based dynamics is employed for a two-wheeled inverted pendulum with the consideration of unknown matched and unmatched uncertainties which are bounded by known nonlinear functions. The model is linearised and further transformed into a regular form to facilitate the analysis and design. A sliding surface is designed, and a set of conditions is developed such that the resulting sliding motion is uniformly ultimately bounded from a practical perspective. Further, a sliding mode control scheme is proposed such that the system is driven to the sliding surface in finite time and maintained on it thereafter. Finally, both simulation and experiment are presented using practical model parameters data to demonstrate the effectiveness and robustness of the regulation control.